EFEKTIVITAS INSTAGRAM SEBAGAI MEDIA PEMBELAJARAN MUFRADAT BERBASIS LITERASI DIGITAL PADA MAHASISWA PENDIDIKAN BAHASA ARAB IAIN SYEKH NURJATI CIREBON - Muhamad Ade Suranto; Septi Gumiandari (CV. ADIBA AISHA AMIRA, 2024)
Instagram can be used to boost students' enthusiasm for learning Arabic because it is an attractive social media platform for today's young generation. This research aims to analyze the effectiveness of Instagram as a digital literacy-based learning medium, including: (1) Analyzing the use of Instagram as a mufradat learning medium for IAIN Syekh Nurjati Cirebon Arabic Language Education Students (2) Analyzing the digital literacy abilities of IAIN Syekh Nurjati Arabic Language Education Students Cirebon (3) Describe the effectiveness of Instagram in learning Arabic language based on digital literacy for Arabic Language Education Students at IAIN Syekh Nurjati Cirebon. Many online platforms and media have proven their effectiveness as recommendations for online-based learning and one of them used for Arabic language education students is the Instagram application. This research uses a qualitative approach, namely the data collected is not in the form of numbers, but manuscripts, interviews, field notes, recordings, and personal documents. The research results show that the Instagram application as a mufradat learning medium is quite effective, quite effective here, namely in using social media as a source of information in searching for materials related to Arabic language learning.